Sandy Ridges System Evolution of Mekong Delta, Southern Vietnam and Its Role in Contructing History of Mekong Delta in Late Holocene - Trang, Nguyen Thi Huyen; Nghi, Tran; Thanh, Dinh Xuan; Nhan, Tran Thi Thanh; Tuyen, Nguyen Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 2DO - 10.25073/2588-1094/vnuees.4247, 2018)
Sandy ridges sytem in the Mekong delta take an importance role in making progading process of delta toward the sea from 5,000 years BP. The generations of sandy ridges are the imprints of the ancient shoreline generations. There are five generations of sandy ridges with the age of 5,000 years, 2,500 years, 1,000 years, 500 years and finally the present sandy ridge which are forming at the modern shoreline. The nearer to the sea is younger. Currently, a series of delta front bars is forming to the south and southeast of river mouths. The delta front bar is predicted to reach 5m high in the next 200 years and connect to the mainland as the present sandy ridge, based on obsolute age data of the ancient sandy ridges. At that time, the Mekong delta will enter a period of intense accretion and the current delta front will turn into a lower delta plain. However, human activities such as hydropower dam construction on the mainstream of the Mekong river and sand exploitation in river channel are causing seriously decrease sediment discharge. Keywords: Sandy ridge, delta front bar, Mekong delta, ancient shoreline.